PRODUCT PLACEMENT DALAM FILM “SURGA YANG TAK DIRINDUKAN” - Salsabela, Fikha Ilmadina (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
The development of communication media today, widely used by entrepreneurs to promote their products. One of the attractive promotional alternatives is to place ads on a film. Movies are able to convey an information and persuade an audience, so advertisers use the film as a promotional medium. This paper aims to convey the results of an analysis of product placement in the film. The object of this research are some products, namely beauty care hand body from Citra brand, Zalora's online shopping app and Biolysin's children's medicine promoted in the film in the movie of "Surga Yang Tak Dirindukan”. The film was directed by Kuntz Agus. In this study, the author uses descriptive qualitative research approach. The results showed that the product placement in accordance with the needs of the scene presented. Promotion through film media, can give understanding of the product to the public. With the understanding of the product, it is expected that people's buying interest will increase. Thus, the film can be one of an effective alternative media to promote products to the potential public.